Energy-aware multipath routing protocol for internet of things using network coding techniques. (14th September 2020) - Sankar, S.; Srinivasan, P.; Ramasubbareddy, Somula; Balamurugan, B.
The energy conservation is a significant challenge to prolong the network lifetime in Internet of Things (IoT). So in this paper, we propose an energy-aware multipath routing protocol (EAM-RPL) to extend the network lifetime. The multipath model establishes multiple paths from the source node to the sink. In EAM-RPL, the source node applies the randomised linear network coding to encode the data packets and it transmits the data packets into the next cluster level of nodes. The intermediate nodes receive the encoded data packets and forward them to the next cluster of nodes. Finally, the sink node receives the data packets and it decodes the original data packet sent by the source node. The performance of the proposed EAM-RPL is compared with the RPL protocol. The simulation result shows that the proposed EAM-RPL improves the packet delivery ratio by 3-5% and prolongs the network lifetime by 5-10%.